EKOS™ Jena Experience: Safety, Feasibility, and Midterm Outcomes of Percutaneous Ultrasound-Assisted Catheter-Directed Thrombolysis in Patients with Intermediate-High-Risk or High-Risk Pulmonary Embolism - Friederike Klein; Sven Möbius-Winkler; Laura Bäz; Rüdiger Pfeifer; Michael Fritzenwanger; Stefan Heymel; Marcus Franz; Pawel Aftanski; P. Christian Schulze; Daniel Kretzschmar (Canadian Respiratory Journal)
Background. Percutaneous catheter-based ultrasound-assisted thrombolysis (UACDT) is recommended for patients with intermediate-high-risk or high-risk pulmonary embolism (PE) in whom systemic thrombolysis has failed or is contraindicated. Aim. To evaluate the safety and efficiency of UACDT in patients with intermediate-high-risk or high-risk PE. Methods. Between October 2017 and January 2020, we performed UACDT using the EkoSonic™ Endovascular System (EKOS™) in 51 patients (21 males, age 63 ± 18 years) with a sPESI of 1.3 ± 0.7. The EKOS™-catheter was implanted within 24 h after admission. Over 15 hours, 11.5 mg of alteplase was administered per catheter. We evaluated right ventricular stress and cardiac biomarkers before and after UACDT. Results. 24 h post-UACDT, median RV/LV ratio decreased from 1.13 to 0.96 (p<0.001) and the mean sPAP decreased from 47 ± 3 to 32 ± 2 mmHg + CVP (p<0.0002). There were 6 major bleeding events resulting in transfusion. No stroke, myocardial infarction, right heart decompensation, or recurrent PE occurred. 31 patients (63%) were discharged without any signs of right ventricular stress. After at least 3 months, 73% of our patients did not show any signs of right ventricular dysfunction. The mean RV/LV ratio decreased to 0.75 ± 0.03 (p<0.0001) in comparison with pre-UACDT, sPAP to 23  mmHg + CVP (p<0.0001), and BNP to 40 pg/ml (p<0.0001). Conclusions. The treatment with UACDT reduced right heart stress during the first 24 hours and midterm in patients with intermediate-high-risk or high-risk PE at an acceptable rate of severe complications.